Clinical evaluation of synthetic computed tomography methods in adaptive proton therapy of lung cancer patients - Taasti, Vicki Trier; Hattu, Djoya; Peeters, Stephanie; van der Salm, Anke; van Loon, Judith; de Ruysscher, Dirk; Nilsson, Rasmus; Andersson, Sebastian; Engwall, Erik; Unipan, Mirko; Canters, Richard (Physics and imaging in radiation oncology, 2023)
•Use of synthetic CTs for adaptive proton therapy of lung cancer patients.•42 patients included, both with and without anatomical changes.•Evaluation of correct adaptation flagging based on synthetic CTs compared to CTs.•Both false positive and false negative rate low, whereby few adaptations are missed.•Reduction of repeat CT acquisitions possible with the use of synthetic CTs. Efficient workflows for adaptive proton therapy are of high importance. This study evaluated the possibility to replace repeat-CTs (reCTs) with synthetic CTs (sCTs), created based on cone-beam CTs (CBCTs), for flagging the need of plan adaptations in intensity-modulated proton therapy (IMPT) treatment of lung cancer patients. Forty-two IMPT patients were retrospectively included. For each patient, one CBCT and a same-day reCT were included. Two commercial sCT methods were applied; one based on CBCT number correction (Cor-sCT), and one based on deformable image registration (DIR-sCT). The clinical reCT workflow (deformable contour propagation and robust dose re-computation) was performed on the reCT as well as the two sCTs. The deformed target contours on the reCT/sCTs were checked by radiation oncologists and edited if needed. A dose-volume-histogram triggered plan adaptation method was compared between the reCT and the sCTs; patients needing a plan adaptation on the reCT but not on the sCT were denoted false negatives. As secondary evaluation, dose-volume-histogram comparison and gamma analysis (2%/2mm) were performed between the reCT and sCTs. There were five false negatives, two for Cor-sCT and three for DIR-sCT. However, three of these were only minor, and one was caused by tumour position differences between the reCT and CBCT and not by sCT quality issues. An average gamma pass rate of 93% was obtained for both sCT methods. Both sCT methods were judged to be of clinical quality and valuable for reducing the amount of reCT acquisitions.